Evolution of homeobox genes: Q50 Paired-like genes founded the Paired class. - Galliot, B.; de Vargas, C.; Miller, D. (Development genes and evolution, 1999)
The genes belonging to the Paired class exert primary developmental functions. They are characterized by six invariant amino acid residues in the homeodomain, while the residue at position 50 can be a serine, glutamine or lysine as in the Pax-type, Q50 Paired-like or the K50 Paired-like homeodomains respectively. Genes in this class emerged early in animal evolution: three distinct Pax genes and two Q50 Paired-like genes have recently been characterised from cnidarians. Phylogenetic molecular reconstructions taking into account homeodomain and paired-domain sequences provide some new perspectives on the evolution of the Paired-class genes. Analysis of 146 Paired-class homeodomains from a wide range of metazoan taxa allowed us to identify 18 families among the three sub-classes from which the aristaless family displays the least diverged position. Both Pax-type and K50 families branch within the Q50 Paired-like sequences implying that these are the most ancestral. Consequently, most Pax genes arose from a Paired-like ancestor, via fusion of a Paired-like homebox gene with a gene encoding only a paired domain; the Cnidaria appear to contain genes representing the 'before' and 'after' fusion events.